Highly active antiretroviral therapy started in infants under 3 months of age: 72-week follow-up for CD4 cell count, viral load and drug resistance outcome. - Aboulker, J; Babiker, A; Chaix, M; Compagnucci, A; Darbyshire, J; Debré, M; Faye, A; Giaquinto, C; Gibb, D; Harper, L; Saïdi, Y; Walker, A (2004)
OBJECTIVE: To assess the feasibility and impact of highly active antiretroviral therapy (HAART) started in vertically HIV-1-infected infants less than 3 months of age. DESIGN: A multicentre, phase I/II, non-randomized, open-label study (PENTA 7). METHODS: Adverse events, plasma HIV-1 RNA, CD4 cell counts, CD4 cell percentage (CD4%) and clinical progression were recorded at baseline and prospectively to 72 weeks in order to assess the toxicity, tolerability and efficacy of a combination of stavudine, didanosine and nelfinavir. Selection of genotypic resistance was also investigated. RESULTS: Twenty infants, of whom only three had Centers for Disease Control and Prevention stage B, initiated HAART at median age 2.5 months (range, 0.9-4.7) with median HIV-1 RNA concentration 5.5 log10 copies/ml (range, 3.2-6.8) and CD4% 33% (range, 11-66). Median follow-up was 96 weeks (range, 60-144). At week 72, 11 infants were still taking the original treatment. Few adverse events were reported related to treatment, all minor and causing treatment interruption in only three infants. No AIDS-defining events occurred; one child died of non-HIV-related causes (prematurity). All but two had CD4% > 25% at 72 weeks; however, 14 infants had virological failure and six acquired resistance mutations. CONCLUSIONS: Early treatment with stavudine, didanosine and nelfinavir was well tolerated and associated with good clinical and immunological outcomes at week 72. However, a high rate of virological failure with emergence of genotypic resistance is of great concern. More palatable drug combinations for infants and closer drug monitoring are required.